SJOGREN SYNDROME AND PAROTID MARGINAL ZONE LYMPHOMA: REPORT OF A CASE AND REVIEW OF LITERATURE. - Francesco Lorusso (Euromediterranean Biomedical Journal, 2020)
Five percent of the cancers in the parotid region are non-hodgkin lymphomas. This lymphoma, involving the mucosa-associated lymphoid tissue (MALT), is called MALToma. A chronic autoimmune inflammatory process of the parotid gland, such as Sjogren's syndrome, results in an increased incidence of parotid MALToma. Biopsy of the parotid is essential for appropriate diagnosis; this can then be completed by radiotherapy, chemotherapy or therapy with monoclonal antibodies according to the stage of the disease. This study shows a clinical case of a 50-year-old patient with Sjogren's syndrome who developed a parotid MALToma.